EuQoS approach for resource allocation in Ethernet networks - Carmo, Maxweel Silva (2007)
Although the equipment currently available for Ethernet LANs provides basic quality of service (QoS) capabilities, as the ability of prioritizing traffic flows, it does not support more complex mechanisms like admission control or the ability of participating in a signalling process. This paper presents a survey on the QoS support and on resource allocation for LAN Ethernet networks, and describes a new proposal in the scope of the EuQoS project. The proposed solution is validated as proof of concept both by simulation and real testbeds. EuQoS is an FP6 IST Integrated Project with the aim of proposing, developing and studying end-to-end QoS support for Internet applications such as voice, video-conferencing, video-streaming and tele-engineering. Copyright © 2007 John Wiley & Sons, Ltd.